Investigating the Stability of eLiposomes at Elevated Temperatures - Husseini, Ghaleb (2014)
eLiposomes encapsulate a perfluorocarbon nanoemulsion droplet inside a liposome. Ultrasound is then used as a trigger mechanism to vaporize the perfluorocarbon, break the liposome, and release the desired drug to the tumor tissue. The purpose of this research is to show that eLiposomes synthesized using perfluoropentane are stable above the normal boiling point of the perfluoropentane and at body temperature and thus has potential for use in vivo. Experiments involving the release of fluorescent calcein molecules were performed on eLiposomes to measure the release of calcein at various temperatures in the absence of ultrasound. Results showed that eLiposomes are stable at body temperatures and that as the temperature increases above 40°C, calcein release from these novel nanocarriers increases.